The problem of J.-J. Rousseau’s influence on the I. Kant’s creative work - A Ju Shachina (RUDN Journal of Philosophy, 2018)
The article shows the continuity in the development of key ideas J.J. Rousseau in the works of Immanuel Kant on the nature of morality and its relation to public morality, the nature of the moral sense and the role of ethics for education. It is shown the main achievements and limitations of the methodological approach by J.J. Rousseau and those aspects of his position that I. Kant developed by their dialectical negation with preservation of the continuity of all the best. Our research involves analysis of primary sources and critical literature. The dialectical method synthesized with the hermeneutical method. The hermeneutical method allows us to understand the system of Rousseau and Kant in their entirety and at the same time to point out the most significant aspects of these theoretical systems. The dialectical method revealed contradictions in the ideas of Rousseau, which prompted Kant to continue these ideas, but already on other grounds. The article discusses how Rousseau influenced Kant in determining the nature of morality through the definition of the essence of the moral law. But at the same time the article shows the differences in the understanding of the moral feeling in Kant and Rousseau: according to Kant, it has its source in pure practical reason, while, according to Rousseau, moral feeling has its source in compassion to the human race (human nature). The conclusion to the article is the statement that major discoveries of Kant in the fields of theoretical reason and of practical reasons were directly prepared by Rousseau, but Kant resolve the contradictions in the attitude of the great “citizen of Geneva”.